You & your aging parent - Barbara Silverstone (Oxford University Press, 2008)
You and Your Aging Parent is a classic--the first book to shed light on the challenging relationship between adult children and their aging parents, illuminating the emotional, health, and financial difficulties that elderly parents and their children face during the senior years